All my tomorrows [large type] : three historical romance novellas of everlasting love - Witemeyer, Karen; Hedlund, Jody; Camden, Elizabeth, 1948- (Thorndike Press, 2018)
Readers journey across America and through time in these moving and romantic stories from top Christian historical romance writers. Karen Witemeyer's "Worth the Wait" takes place at Harper's Station women's colony, where a young mother faces the past in order to trust again. In Jody Hedlund's "An Awakened Heart," a young woman and a new minister spar over how to help the needy in New York's tenements. And in Elizabeth Camden's "Toward the Sunrise," a female medical student's decision leaves her at the mercy of a stubborn but handsome attorney.